Republic of Estonia : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
Estonia has succeeded in reducing its macroeconomic imbalances and vulnerabilities, but faces the challenge of preserving its hard-earned fiscal and financial stability and enhancing long-term growth prospects. In this regard, adopting a fully fledged medium-term fiscal framework can help assess policy trade-offs and avoid procyclical policies. Financial sector stability can be safeguarded by strengthening macroprudential policies. Deeper Nordic-Baltic cross-border prudential arrangements and the EU banking union can enhance financial stability. Estonia needs to safeguard its external competitiveness, address skill mismatches, and accelerate human capital accumulation.